Physioethology: a post-humanist perspective on physiotherapy - Low, Matthew; Moffatt, Fiona H.; Kerry, Roger; Nicholls, David A. (Physiotherapy theory and practice, 2025)
Physiotherapy faces mounting challenges in an era of planetary crisis. This paper proposes a reorientation of physiotherapy through the philosophy of Gilles Deleuze and Félix Guattari, specifically their concept of ethology, which foregrounds affect, relation, and immanence. We argue that contemporary physiotherapy remains tethered to anthropocentric, essentialist, and representational assumptions that limit its capacity to respond to complex ecological entanglements. Drawing on ethology, we explore how bodies, human and non-human, can be understood not as stable entities but as dynamic assemblages defined by what they can do. We consider the implications of this approach for practice, education, and planetary health, suggesting that physiotherapy shift from its traditional forms of praxis toward a dynamic composition of capacities. In doing so, the profession might cultivate an ecologically attuned, affectively sensitive, and experimentally oriented practice capable of engaging in the world.